High Performance NIR OLEDs with Emission Peak Beyond 760 nm and Maximum EQE of 6.39%. Issue 17 (15th June 2022) - Zhang, Hongyang; Chen, Zhao; Zhu, Longzhi; Wu, Yongquan; Xu, Yuqing; Chen, Shuming; Wong, Wai‐Yeung
Abstract: Advances in achieving high external quantum efficiency (EQE) of near‐infrared (NIR) organic light‐emitting diodes (OLEDs) are lagging behind that of the visible‐light OLEDs, according to the energy gap law. Herein, two structurally simple NIR‐phosphorescent Ir(III) complexes, DTCNIr and PTCNIr, with the cyclometalated ligands functionalized by the 1‐phenylisoquinoline‐4‐carbonitrile moiety and thieno/benzo[ b ]thiophene moiety are handily accessed within three synthetic steps. The introduction of the cyano unit can significantly lower the lowest unoccupied molecular orbitals whereas incorporating the conjugated group can elevate the highest occupied molecular orbitals of the newly designed Ir(III) complexes. The intramolecular charge transfer (ICT) transitions are enhanced due to the increased donor–acceptor interaction inside the metallophosphor. As a result, the emissions are red‐shifted to the NIR region with fast radiative decay. A maximum external quantum efficiency (EQE) of 8.11% with the emission peak at 726 nm for DTCNIr and a maximum EQE of 6.39% with the emission peak at 763 nm for PTCNIr are achieved in the NIR OLEDs by using these Ir(III) materials as the dopant emitters, a champion efficiency in the Ir(III)‐based OLEDs with the emission peak exceeding 760 nm. Abstract : By functionalizing the isoquinolyl and thienyl units of cyclometalated ligands, the newly designed Ir(III) emitters afford the champion efficiency in the Ir(III)‐based OLEDs with the electroluminescent peak exceeding 760 nm.